2014
DOI: 10.1186/1758-5996-6-130
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and oxidative stress markers in Wistar rats after 2 months on a high-fat diet

Abstract: BackgroundMetabolic syndrome is associated with an increased risk of cardiovascular and hepatic complications. Oxidative stress in metabolic tissues has emerged as a universal feature of metabolic syndrome and its co-morbidities. We aimed to develop a rapidly and easily induced model of metabolic syndrome in rats to evaluate its impact on plasma and tissue oxidative stress.Materials and methodsMetabolic syndrome was induced in rats using a high-fat diet (HFD), and these rats were compared to rats fed a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
41
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 48 publications
12
41
3
4
Order By: Relevance
“…Interestingly, the increase in liver triacylglycerol concentrations occurred independently of any changes in fasting plasma triacylglycerol, as plasma levels were previously found to be normal (Sweazea et al, ). These findings are in contrast with studies that administered adult rats a mixed high‐carbohydrate and HFD for longer durations (Auberval et al, ).…”
Section: Discussioncontrasting
confidence: 88%
“…Interestingly, the increase in liver triacylglycerol concentrations occurred independently of any changes in fasting plasma triacylglycerol, as plasma levels were previously found to be normal (Sweazea et al, ). These findings are in contrast with studies that administered adult rats a mixed high‐carbohydrate and HFD for longer durations (Auberval et al, ).…”
Section: Discussioncontrasting
confidence: 88%
“…Oxidative stress in rats due to high fat diet feeding also increases the glucose intolerance and insulin resistance [42, 43]. Our investigation also revealed that high fat diet increased plasma and tissues level of oxidative stress markers.…”
Section: Discussionsupporting
confidence: 55%
“…The importance of treatment intervals on tissue and plasma oxidative stress levels was emphasized in several studies. Auberval et al . demonstrated that although short‐term high‐fat diet (HFD) exhibits oxidative stress on pancreatic and hepatic tissues, this effect was not valid for plasma oxidative stress markers.…”
Section: Discussionmentioning
confidence: 99%